Extraction and Medical Coding of Adverse Events using Word Embedding - Sarkar, Rajdeep; Sampale, Devyani; Rai, Harshita (International Journal of Computer Sciences and Engineering, 2025)
Machine based identification and coding of Adverse Events mentioned in the natural language text received in Pharmacovigilance through the different sources be it emails, faxes, literature, complaint reports, forms, study literatures or phone call transcripts poses a compound problem as it deals with two sub problems, firstly Named entity recognition to detect events (symptoms, illnesses, adverse events) and secondly mapping events to a standard medical coding scheme such as MedDRA. Additionally, industrial applications are required to build their systems in compliance with regulatory requirements, thereby limiting their ability. In this paper we focus on mapping laymen terms or adverse event verbatim/ description to the standard medical terms. We use vector representation of standard medical term dictionary Medical Dictionary for Regulatory Activities (MedDRA) and that of the event verbatim along with their similarity score to establish these mappings.